Bühlmann's Credibility Model with Claims of Negative Binomial and 2-Poisson Distribution - Maulidi, Ikhsan; Apriliani, Vina (Mathematics Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
One of the premium determination techniques is to use credibility theory. In this study, a credibility premium determination model was derived with the best accuracy approach in the form of Bühlmann’s credibility premium. The claim data is assumed to have a Negative Binomial and 2-Poisson distribution. Bühlmann's credibility premium formula is given explicitly for these two data distributions. The obtained model is also applied to the correct data following these distributions. From the simulation results, it is obtained that the premium values are very close in value so that both models can be applied to the data and have a high level of credibility because they have a high credibility factor value.